Prevention Stunting in Desa Kasiyan through MPASI Education and Nutritious Food with 019 Collaborative KKN Students - Kansha Hasri Ainun; Intan Fauza Az-Zahra; Lisa Qurrotu Aini; Wardatus Sholehah; Ahmad Jailani; Dina Via Rakhmatul Hikhmah (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2024)
Stunting describes a state of chronic lack of nutritional status that occurs during a period of growth and development from an early age. Stunting is one of the problems currently being the focus of the Indonesian government. Stunting prevention efforts can be started from the surrounding environment through education from related parties. This encourages the Jember Collaborative KKN team to help with problems in the community. There are various factors that can lead to stunting in children under five, including the individual characteristics of toddlers and socioeconomic aspects. This research was conducted as an observation in Kasiyan Village, Puger District, Jember Regency. Due to the lack of knowledge of the villagers about stunting, the Jember Collaborative KKN students worked together with the village government to invite the residents back to counseling activities to prevent stunting. This activity includes information on steps to prevent and treat stunting. In addition, it also explains the impact of gaps that may arise if a clean and healthy lifestyle is not implemented, which can contribute to stunting in children. Jember Collaborative KKN students also conducted demonstrations to villagers, especially mothers, regarding how to provide complementary food for ASI (breast milk) that is suitable, economical, and easy to obtain from the surrounding environment. From this activity, students hope to achieve results and goals, namely the high enthusiasm of the residents so that extension activities can run smoothly. Villagers no longer feel alien to the concept of stunting and have knowledge on how to prevent it, including proper complementary feeding. It is hoped that this new knowledge will be able to be applied by the target community to provide the needs of solids and nutritious food for the baby. This activity begins with organizing in the form of a Business Model Canvas (BMC) and then proceeds to the process in the field.